The Influence of Organizational Culture on Employee Productivity in Multinational Companies - Josep Purba (Patua : Journal of Business Administration and Management, 2024)
This study aims to analyze the influence of organizational culture on employee productivity in multinational companies. The research method used is a quantitative approach with an associative research type. Data were collected by distributing questionnaires to 100 respondents who are employees of multinational companies, with a sampling technique using simple random sampling. Data analysis was performed using simple linear regression with the help of statistical software. The results of the study indicate that organizational culture has a positive and significant effect on employee productivity, with a significance value of 0.000 < 0.05 and a regression coefficient of 0.678. The coefficient of determination (R²) value of 0.612 indicates that organizational culture is able to explain 61.2% of the variation in employee productivity. This indicates that organizational culture is an important factor in improving employee performance. This study provides implications that multinational companies need to build and maintain a strong, adaptive, and inclusive organizational culture to increase employee productivity and company competitiveness at the global level.